CSF Markers of Oxidative Stress Are Associated with Brain Atrophy and Iron Accumulation in a 2-Year Longitudinal Cohort of Early MS - Burgetova, Andrea; Dusek, Petr; Uher, Tomas; Vaneckova, Manuela; Vejrazka, Martin; Burgetova, Romana; Horakova, Dana; Srpova, Barbora; Kalousova, Marta; Noskova, Libuse; Levova, Katerina; Krasensky, Jan; et al. (International journal of molecular sciences, 2023)
In this prospective longitudinal study, we quantified regional brain volume and susceptibility changes during the first two years after the diagnosis of multiple sclerosis (MS) and identified their association with cerebrospinal fluid (CSF) markers at baseline. Seventy patients underwent MRI (T1 and susceptibility weighted images processed to quantitative susceptibility maps, QSM) with neurological examination at the diagnosis and after two years. In CSF obtained at baseline, the levels of oxidative stress, products of lipid peroxidation, and neurofilaments light chain (NfL) were determined. Brain volumetry and QSM were compared with a group of 58 healthy controls. In MS patients, regional atrophy was identified in the striatum, thalamus, and substantia nigra. Magnetic susceptibility increased in the striatum, globus pallidus, and dentate and decreased in the thalamus. Compared to controls, MS patients developed greater atrophy of the thalamus, and a greater increase in susceptibility in the caudate, putamen, globus pallidus and a decrease in the thalamus. Of the multiple calculated correlations, only the decrease in brain parenchymal fraction, total white matter, and thalamic volume in MS patients negatively correlated with increased NfL in CSF. Additionally, negative correlation was found between QSM value in the substantia nigra and peroxiredoxin-2, and QSM value in the dentate and lipid peroxidation levels.
Keywords: longitudinální studie; Central Nervous System Diseases; cerebrospinal fluid; roztroušená skleróza; Gray Matter; iron; Oxidative Stress; mozek; železo; Prospective Studies; magnetic resonance imaging; atrofie; magnetická rezonanční tomografie; Multiple Sclerosis; Iron; Brain; Magnetic Resonance Imaging; oxidative stress; šedá hmota; Humans; prospektivní studie; susceptibility; Longitudinal Studies; oxidační stres; nemoci centrálního nervového systému; lidé; Atrophy; multiple sclerosis